The Characteristic of Metabolic Changes at Insulin Resistance in Children with Primary Hypertension - N.N. Kaladze; O.K. Alyoshina; N.A. Revenko (Zaslavsky O.Yu., 2013)
In children with hypertension we identified various metabolic disorders and the role of insulin resistance in their development, as well as compensatory mechanisms of maintaining normoglycemia.